Settlement Sites with Middle Neolithic Houses at Grødby, Bornholm - Kempfner-Jørgensen, Lars; Watt, Margrethe (Journal of Danish Archaeology, 1985)
Settlement Sites with Middle Neolithic Houses at Grødby, Bornholm